Observations of Phobos by the Mars Express radar MARSIS: Description of the detection techniques and preliminary results. Issue 10 (15th November 2017) - Cicchetti, A.; Nenna, C.; Plaut, J.J.; Plettemeier, D.; Noschese, R.; Cartacci, M.; Orosei, R.
Highlights: For the first time we observed Phobos, with a spaceborne radar (MARSIS). We re-configured the MARSIS radar, originally designed to operate exclusively on Mars, in order to observe Phobos. We collected data of high scientific interest. Abstract: The Mars Advanced Radar for Subsurface and Ionosphere Sounding (MARSIS) (Picardi et al., 2005) is a synthetic aperture low frequency radar altimeter, onboard the ESA Mars Express orbiter, launched in June 2003. It is the first and so far the only spaceborne radar that has observed the Martian moon Phobos. Radar echoes were collected on different flyby trajectories. The primary aim of sounding Phobos is to prove the feasibility of deep sounding, into its subsurface. MARSIS is optimized for deep penetration investigations and is capable of transmitting at four different bands between 1.3 MHz and 5.5 MHz with a 1 MHz bandwidth. Unfortunately the instrument was originally designed to operate exclusively on Mars, assuming that Phobos would not be observed. Following this assumption, a protection mechanism was implemented in the hardware (HW) to maintain a minimum time separation between transmission and reception phases of the radar. This limitation does not have any impact on Mars observation but it prevented the observation of Phobos. In order to successfully operate the instrument at Phobos, a particular configuration of the MARSIS onboard software (SW) parameters, called "Range Ambiguity, " was implemented to override the HW protection zone, ensuring at the same time a high level of safety of the instrument. This paper describes the principles of MARSIS onboard processing, and the procedure through which the parameters of the processing software were tuned to observe targets below the minimum distance allowed by hardware. Some preliminary results of data analysis will be shown, with the support of radar echo simulations. A qualitative comparison between the simulated results and the actual data, does not support the detection of subsurface reflectors.